Calculation of Flight Data Fusion Coefficients Using Newton–Raphson Iterations (Моделювання, керування та інформаційні технології, 2020)
The problem of plotting the flight path of an aircraft based on flight data containing numerous measurement errors is investigated. A theoretical (continuous) model of the flight data fusion problem is proposed in the form of a boundary value problem for a system of differential equations with unknown coefficients. The application of the Newton–Raphson iteration method for calculating the sought-for coefficients is described.